2019
DOI: 10.1167/iovs.19-27135
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Inner Retinal Hyperreflective Alterations in Early Cognitive Impairment on Adaptive Optics Scanning Laser Ophthalmoscopy

Abstract: PURPOSE. To examine inner retinal hyperreflective features on adaptive optics scanning laser ophthalmoscopy (AOSLO) in individuals with early cognitive impairment. METHODS. In this prospective, cross-sectional study, we enrolled 12 participants with either amnestic mild cognitive impairment (aMCI, n ¼ 10) or early dementia due to Alzheimer's disease (eAD, n ¼ 2) and 12 age-, sex-, and race-matched cognitively normal controls. All participants completed AOSLO imaging of the inner retina. AOSLO montages of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 55 publications
2
19
0
Order By: Relevance
“…Sixty-one (86%) studies used a form of neurocognitive testing (eg Mini-Mental State Examination (MMSE), Montreal Cognitive Assessment (MOCA), etc. ), 17–34 , 36–44 , 46 , 47 , 49–80 56 (79%) relied on clinical diagnosis by experts based on criteria such as the DSM-IV or NINCDS-ADRDA, 18 , 20 , 21 , 24 , 26–34 , 36 , 39 , 41–44 , 46–52 , 54–57 , 62–64 , 66–88 29 (41%) utilized neuroimaging techniques (eg magnetic resonance imaging (MRI), computed tomography (CT) scan, or PET), 18 , 19 , 21–23 , 25 , 29–31 , 33 , 34 , 37 , 39–41 , 44 , 46 , 48 , 49 , 51 , 53 , 56 , 57 , 60 , 61 , 66 , 68 , 75 , 79 and 13 (18%) used immunohistochemical staining for biomarkers tau and amyloid. 21–23 , 25 , 31 , 32 , 34 , 35 , 37 , 39 , 50 , 51 , 61 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Sixty-one (86%) studies used a form of neurocognitive testing (eg Mini-Mental State Examination (MMSE), Montreal Cognitive Assessment (MOCA), etc. ), 17–34 , 36–44 , 46 , 47 , 49–80 56 (79%) relied on clinical diagnosis by experts based on criteria such as the DSM-IV or NINCDS-ADRDA, 18 , 20 , 21 , 24 , 26–34 , 36 , 39 , 41–44 , 46–52 , 54–57 , 62–64 , 66–88 29 (41%) utilized neuroimaging techniques (eg magnetic resonance imaging (MRI), computed tomography (CT) scan, or PET), 18 , 19 , 21–23 , 25 , 29–31 , 33 , 34 , 37 , 39–41 , 44 , 46 , 48 , 49 , 51 , 53 , 56 , 57 , 60 , 61 , 66 , 68 , 75 , 79 and 13 (18%) used immunohistochemical staining for biomarkers tau and amyloid. 21–23 , 25 , 31 , 32 , 34 , 35 , 37 , 39 , 50 , 51 , 61 …”
Section: Resultsmentioning
confidence: 99%
“… 29 , 57 , 83 However, there is great variability among these studies, perhaps due to their sample sizes and the broad definitions of MCI for which there are multiple subtypes (eg amnestic and non-amnestic MCI). Studies including only amnestic MCI are more relevant to the study of AD, 28 , 39 , 44 , 51 , 52 , 57 , 65 , 75 , 76 , 81 but a number of the studies did not specify which subtype of MCI was included. 24 , 26 , 27 , 29 , 30 , 37 , 41 , 42 , 46–48 , 54 , 56 , 78 , 83 Further exploration of these imaging tools as screening measures for pre-clinical neurodegenerative changes is warranted, especially in larger cohorts of amnestic MCI patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies have also reported macular thickening in moderate stage AD (Salobrar-García et al, 2019 ). These findings may be a result of inflammatory changes triggered by amyloid deposition or development of granular membranes secondary to retinal gliosis (Zhang et al, 2019a ). Although the timeline of these changes is unclear, the proposed dynamic nature of the retina may partially explain negative OCT studies, which examine retinal thickness across pre-set areas.…”
Section: Afferent Visual Biomarkersmentioning
confidence: 99%